2022
DOI: 10.56498/422022413
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging as a Resource for Teaching and Assessment:

Abstract: The scant research on translanguaging in teaching and assessment in senior high school contexts in the Philippines prompted this research to explore the perception of teachers of classes where English is the required medium of instruction.  The present study investigated the perspectives of 24 senior high school (SHS) English teachers in a focus group discussion from selected schools in Region VI-A, Philippines and 65 SHS teachers who completed a survey questionnaire adapted and modified from the studies of Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
0
0
Order By: Relevance
“…Translanguaging and teacher authority also connect with assessment. Plata and Macawile (2022) found that teachers are willing to incorporate translanguaging into their formative (initial, explorative) but not summative (final, mark-based) assessments. Jaspers (2018) tells us that regardless of how much we embrace translanguaging, students continue to be formally assessed based on monolingualism and academic language.…”
Section: Introductionmentioning
confidence: 99%
“…Translanguaging and teacher authority also connect with assessment. Plata and Macawile (2022) found that teachers are willing to incorporate translanguaging into their formative (initial, explorative) but not summative (final, mark-based) assessments. Jaspers (2018) tells us that regardless of how much we embrace translanguaging, students continue to be formally assessed based on monolingualism and academic language.…”
Section: Introductionmentioning
confidence: 99%